1999
DOI: 10.1007/s001050050963
|View full text |Cite
|
Sign up to set email alerts
|

Fokale akrale Hyperkeratose

Abstract: Focal acral hyperkeratosis is a disorder characterized by hyperkeratotic papules along the border of the hands and feet. Focal acral hyperkeratosis and several marginal punctate keratodermas closely resemble acrokeratoelastoidosis of Costa. The question if there is a difference between acrokeratoelastoidosis of Costa and focal acral hyperkeratosis or if they are variants of the same entity are discussed. We report a case showing focal acral hyperkeratosis, review the clinical and histological features of relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…To the best of our knowledge, such histopathologic abnormalities have not yet been described in FAH. Thus, we think that FAH and acrokeratoelastoidosis are separate entities, a notion that is in line with the opinion of other groups 2,5–7 …”
supporting
confidence: 86%
See 4 more Smart Citations
“…To the best of our knowledge, such histopathologic abnormalities have not yet been described in FAH. Thus, we think that FAH and acrokeratoelastoidosis are separate entities, a notion that is in line with the opinion of other groups 2,5–7 …”
supporting
confidence: 86%
“…Furthermore, the authors note that we recently reported on a patient with acrokeratoelastoidosis, 3 a disease closely resembling FAH 2,4,5 . By coincidence, our patient also showed a striking onychodystrophy affecting all her nails.…”
supporting
confidence: 66%
See 3 more Smart Citations